Innovation and adaptation in public–private partnerships in the military domain under broad-spectrum influencing: Towards a competence-based strategic approach - Häyhtiö, Markus; Eklund, Amanda; Palokangas, Marko (Journal of military studies, 2024)
The purpose of this research is to conduct two instrumental case studies, one from Finland and the other from Israel. These case studies explain ‘why’ and ‘how’ clear and significant differences exist between these two nations in the area of military innovation and adaptation. Research strategy is not to conduct a comparative case study, but results make it possible to find and evaluate operating methods suitable for building and safeguarding Finnish society in cooperation between private and public actors. The operating methods being studied focus on the early stages in the life cycle of developing military capability. This study utilises the inductive approach, in which data guide the research process. As the research progresses, new information is built on top of the acquired data, and the overall picture of the topic is constructed in an iterative manner. Contribution of the research are propositions that the Finnish Defence Forces would benefit from a competence-based strategic approach to partially replace the resource-based approach. A separate sub-strategy with its foundation in competence-based strategy is proposed for innovation activities. Results indicate that the excellence-based approach chosen by Israel that emerged in the case study and literature review has specifically produced results in the area of developing innovation activities.